PENGARUH UKURAN PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP EARNINGS MANAGEMENT SERTA DAMPAKNYA TERHADAP EARNINGS QUALITY - Arbaleta Griselda; Julianti Sjarief (Jurnal Akuntansi, 2019)
This research is conducted to analyze the effect of company size and corporate governance (proportion of independent commissioner and size of board of directors) on earnings management and its impact on earnings quality. This test consists of two research models. The first research model analyzes the effect of company size, proportion of independent commissioner, and size of board of directors on earnings management, while the second research model analyzes the effect of earnings management on earnings quality. The object of this research are manufacturing companies that are listed on Indonesia Stock Exchange (IDX) in 2015-2017. The number of samples used for the first research model is 194 sample data and the second research model is 181 sample data. This study was conducted by using multiple linear regression analysis on the first research model and simple regression analysis on the second research model. The result of the first research model analysis shows that company size has an effect on earnings management, while the proportion of independent commissioners and the size of the board of directors have no effect on earnings management variable. And then, the result of the second research model analysis shows that earnings management has an effect on earnings quality.